Effectiveness of nursing interventions on level of anxiety, stress, and depression of elderly patients undergoing upper gastrointestinal endoscopy - Refaat Alam, Raefa; Ibrahim Elemam Elashri, Neamit (International Journal of Advanced Nursing Studies, 2020)
Background: Gastrointestinal Endoscopy is a widely used procedure in medicine today. It is the diagnosis and treatment of choice among elderly patients with upper gastrointestinal disorders. Thus anxiety, stress, and depression of adverse out-come or side effect and discomfort regarding endoscopy reduce the patient’s acceptance ability. Effective procedure ex-planation and safety measures have positively impact on decrease level of anxiety, stress, and depression and improve elderly patient’s general health condition Aim: Evaluate effectiveness of nursing interventions on level of anxiety, stress and depression of elderly patients undergoing upper gastrointestinal endoscopy. Design: A quasi experimental study design with pre and post procedure was used.Setting: The study was conducted at Gastrointestinal Surgery Center (GISC) (Endoscopy Unit) Mansoura University Subjects: A convenient sample of 76 elderly patients undergoing GIT endoscopy. Data collected over a period of 9 months from first of May 2019 at the end of January 2020.Tools: Three tools were used: Socio Demographic Characteristics and Clinical Data Structured Interview Schedule, Depression, Anxiety and Stress scales (DASS-21), and Endoscopic Nursing interventions.Results: The study results revealed that statistically significant improvement in all aspects of elderly patient's anxiety score at pre and post nursing intervention (p<0.001). There were significant improvements of level of stress from pre and post implementation of nursing intervention to endoscopy (p<0.05). Also, there was a statistically significant difference in the pre, and posttest mean score of depression (p<0.05). Statistically significant differences regarding all sociodemographic characteristics within the studied subjects and their total mean score of anxiety, stress, and depression.Conclusion A clear and noticeable improvement in the mean score of anxiety, stress and depression of all studied subject after the implementation of the endoscopic nursing interventions than before.Recommendation: Replication of this study is highly recommended on a large representative probability sample to achieve generalizable results.